Teaching of higher order thinking skills in the mathematics classroom among primary school mathematics teachers in Temerloh, Pahang, Malaysia - Chandran, Tamilarasi (2022)
Higher order thinking skills act as crucial component skills to face worldwide competition in this rapid information era. Ministry of Education (2013) defined higher order thinking skills (HOTS) as the capability to apply knowledge, problem solving, reflection, value reasoning, reasoning skills, innovating something new and decision making. Teachers are responsible to instill the learning of HOTS to instigate activities which requires deeper thinking among students in the pedagogy of 21st century. Nevertheless, not much research has been conducted pertaining to the teaching of Higher Oder Thinking Skills, and the factors that may influence in teaching of HOTS among teachers as not many comprehensive studies have been done in relation to this. The purpose of this study is to determine factors influencing to the teaching of HOTS in mathematics classroom. This study looked at teachers’ knowledge of HOTS; teachers’ pedagogical skill; teachers’ attitude; barriers in teaching higher order thinking skills in mathematics class. This study used a correlation research design carried out on 71 primary schools in Temerloh district. Cochran’s formula stratified random sampling technique was used to select 269 teachers for this study. The respondents were selected by using proportional stratified random sampling technique. Data were collected using a set of questionnaire, which was adapted from previous studies and validated by a panel of expert. The obtained data were analyzed using SPSS statistical software version 19. Descriptive statistics were used to assess the demographic profile of the Mathematics teachers of Temerloh district. Subsequently, Pearson-Product moment correlation was used to identify the relationship between independent and dependent variables. The multiple regression analysis was also employed to predict the factors influencing to the teaching of HOTS in mathematics classroom. The results revealed that the majority of mathematic teachers self-reported a moderate to high level of teaching HOTS. The analysis showed that majority of the teachers agreed that how to stratify the learning components to the level of the students for teaching HOTS (M = 3.79, SD = 0.38). In addition, the teachers’ reported that they are able to use different strategies and techniques to teach HOTS in mathematics classroom (M=3.94 , SD=0.43). Moreover, the teachers were found to have a positive attitude towards teaching of HOTS (M=3.74,SD=0.49). In terms of barriers, the finding revealed that the teachers merely faced slight problem due to the teachers related barriers, students related barriers, and external related barriers. Positive significant correlations existed between the level of HOTS usage and the four factors. The multiple regression analysis revealed that all the four factors influencing were found to be significant in predicting the level of teaching HOTS among mathematics teachers.